The Role of Social Media and Digital Platforms in the Formation of Religious Identity Among Young People in Albania (Context: Journal of Interdisciplinary Studies, 2025)
This article examines models of the description and classification of the sciences among the Ottomans in the 15th century. It considers the importance of the works of Mehmed Şah Fenârîzâde, ʿAbd al-Raḥmān al-Bistāmī and Mollā Luṭfī for the classification of the sciences in the 15th-century Ottoman context. Different authors adopted distinct theoretical perspectives and methodological approaches to the subject. The analysis partly addresses the genre of unmūḏağ literature as a particular model for describing scientific disciplines, as well as ceThis article examines the relationship between religion and digital identity among young Albanian Muslims. The aim of the paper is to understand how social media and digital platforms influence the formation and affirmation of religious identity of Albanians online. Methodologically, the study combines social media monitoring (including Facebook, Instagram, and YouTube) of online mosque accounts, several religious influencers, and their followers, with a survey of 100 young people aged 15-35. Existing literature, such as Hoover, Clark, Campbell, Lövheim and Tsuria, describe this phenomenon as „digital religion,” emphasizing the ways in which online spaces foster spiritual exploration, community belonging, and the negotiation of religious identity. The findings show that digital platforms offer young people access to diverse religious content, peer support, and participation in virtual faith communities, helping strengthen religious commitment and build a conscious religious identity. However, the modest sample used here provides only an initial indication of current trends. Future research should expand this area with surveys, interviews, and comparative studies at the regional (Balkan) level. This study makes an original contribution to the Albanian context, providing the first empirical analysis of how young Muslims interact with their faith in the digital age.rtain phenomena related to the introduction of new methodological approaches and new ways of conceptualizing the notion of ʿilm within the Ottoman literary tradition of the period. The tendency to relativize certain scientific fields in particular types of literature could partially influence the development of some disciplines while contributing to the neglect of others. The struggle for dominance of a given educational paradigm depended on both the foundational principles upon which the relevant institutions were established and the literature selected and canonized during the formulation of curricula at the time of their founding.